IoT-Based Plant Irrigation System in the Setu Babakan Tourism Area Landscape - Waskita Cahya; Filda Angellia; Yuli Prasetya; M. Febriansyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Sustainability of green landscape management in the Setu Babakan tourism and recreation area is threatened by low-efficiency water use and a suboptimal system of plant care. In the age of the internet, the Internet of Things (IoT) presents us with a modern solution to a manual watering system. This study focuses on developing and deploying an IoT-supported plant watering system to create an environmentally-friendly and scenic view of tourist attractions. The device has a sprinkler head, an ESP32 microcontroller and a soil moisture probe to monitor soil condition. The collected information is sent to a server through MQTT. The data is presented on a web platform that can be accessed from a computer and smartphone. This research methodology includes hardware, software, and field testing developments. The findings show that when the soil is dry, the system can automate plant watering and control soil moisture quality, saving labor. Low investment, flexible construction, high efficiency. This system can improve landscape management efficiency, but also promote the sustainable development of tourist destinations. The importance of this subject in relation to environmental protection and the modern means and methods of environmental protection technology is obvious. The originality of this work is that an IoT-based watering system in the Setu Babakan tourist area could increase 35% of water use efficiency compared to conventional watering (control), p < 0.05 (statistically significant difference), which indicates that this IoT-based watering system could make resource and plant health conservation in the Setu Babakan area.